2021
DOI: 10.3390/cancers13163929
|View full text |Cite
|
Sign up to set email alerts
|

Maturation State-Specific Alternative Splicing in FLT3-ITD and NPM1 Mutated AML

Abstract: Despite substantial progress achieved in unraveling the genetics of AML in the past decade, its treatment outcome has not substantially improved. Therefore, it is important to better understand how genetic mutations translate to phenotypic features of AML cells to further improve response predictions and to find innovative therapeutic approaches. In this respect, aberrant splicing is a crucial contributor to the pathogenesis of hematological malignancies. Thus far, altered splicing is well characterized in rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…Next, given the possible functional consequences of splicing changes between the identified tiles in many AML associated genes, we hypothesized that our splicing based patient grouping could improve clinical decisions that are based on mutation analysis alone. Notably, the added value of splicing changes to AML classification has been shown recently for FLT3 -ITD and NPM1 for FAB classification AML genes 38 as well as RUNX1 and SF3B1 39 . To assess usefulness of combining splicing changes and mutations to predict drug response, we prioritize FLT3 -ITD and Sorafenib and NPM1 and Venetoclax due to reliable mutation calls and their prominent role in AML clinical diagnosis.…”
Section: Resultsmentioning
confidence: 87%
“…Next, given the possible functional consequences of splicing changes between the identified tiles in many AML associated genes, we hypothesized that our splicing based patient grouping could improve clinical decisions that are based on mutation analysis alone. Notably, the added value of splicing changes to AML classification has been shown recently for FLT3 -ITD and NPM1 for FAB classification AML genes 38 as well as RUNX1 and SF3B1 39 . To assess usefulness of combining splicing changes and mutations to predict drug response, we prioritize FLT3 -ITD and Sorafenib and NPM1 and Venetoclax due to reliable mutation calls and their prominent role in AML clinical diagnosis.…”
Section: Resultsmentioning
confidence: 87%
“…Recently, Wojtuszkiewicz et al found that there is maturation state-specific differential splicing of genes associated with cell cycle control and DNA damage in FLT3 -ITD and NPM1 -mutated AML blasts. Intriguingly, the number of genes that displayed differential splicing was significantly higher in the FAB M4 subtype, with a total of 1438 splicing events, compared with the FAB M1 and M2 subtypes, each with about 200 splicing events [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Actually, the enrichment analysis also reveals links to other interleukins as 4, 13 and 20 families, further suggesting a relationship with immunoregulatory processes and in ammation that would mark the tumor microenvironment. Finally, FTL3 tyrosine kinase receptor mechanisms have been linked to a variety of tumors, including hepatocellular carcinoma [40] and acute myeloid leukemia [41]. In the latter, it is worth noting that the numerous splicing-related alterations have enabled to establish different tumors groups, based on the pathways to which differentially spliced genes belong.…”
Section: Discussionmentioning
confidence: 99%